Morphology of the last instar larva and pupa of Synanthedon caucasica (Gorbunov, 1986) (Lepidoptera: Sesiidae), a serious pest of oriental plane and elm trees - Bąkowski, Marek; Karimzadeh, Javad (Zootaxa, 2021)
This work presents the first description of the morphology of the last larval instar and pupa of the clearwing moth species Synanthedon caucasica (Gorbunov, 1986). All diagnostic morphological characters are described in detail, compared with the closely related species Synanthedon loranthi (Králíček, 1966), and these diagnostic characters are illustrated with photographs and line drawings.